Physiological and morphological responses of grass species to drought - Bachle, Seton (Kansas State University, 2017)
The impacts of climate change over the next 100 years on North American grasslands are unknown. Climate change is projected to increase rainfall and seasonal temperature variability, leading to increased frequency of drought and decreased rainfall amounts for many grassland locations in the central Great Plains of North America. To increase our ability to predict the effects of a changing climate, I measured multiple morphological and physiological responses from a diverse suite of C3 and C4 grasses. Due to varying characteristics associated with the different photosynthetic pathways, these grass species respond differently to altered temperature and precipitation. I monitored grass physiology and microanatomy in conjunction with varying watered availability to replicate drought. In the second chapter, I observed leaf-level physiology and root level morphology of C3 and C4 grasses when exposed to 100% water reduction. Results indicated that response to water reduction are not always dependent on the photosynthetic pathway. Root-level morphological measurements were found to vary significantly between species in the same genus; F. ovina had the highest specific root length (SRL), which is an indicator of tolerance to environmental variability. Results also indicated that grasses of interest have thresholds that when passed result in a photosynthetically inactive plant; however it was shown that they are able to recover to near pre-drought gas exchange rates when water is re-applied. The third chapter investigated both leaf-level physiology and morphology in dominant C4¬ grasses across Kansas’ rainfall gradient over the growing season. I hypothesized that variation within a species’ physiology would be greater than its’ morphology. I also hypothesized that morphology would predict variability in a species physiological response to changes in climate. This research discovered within a location and species, leaf morphology is fixed across the growing season. Strong correlations between leaf physiology and morphology were observed, however, the strength and relationship changed among the species compared. A. gerardii and P. virgatum exhibited opposing relationships when comparing their photosynthetic rates to the amount of bundle sheath cells. This result highlights strong species-specific relationship between physiology and morphology. My results illustrate the importance of utilizing plant physiology and morphology to understand how grasses may respond to future climate change scenarios.
Keywords: Ecophysiology; Grasslands; Climate change; Tallgrass prairie; Drought; Great Plains